2017
DOI: 10.1111/bjop.12258
|View full text |Cite
|
Sign up to set email alerts
|

Beauty in the blink of an eye: The time course of aesthetic experiences

Abstract: Under normal circumstances, perception runs very fast and seemingly automatic. In just a few ms, we go from sensory features to perceiving objects. This fast time course does not only apply to general perceptual aspects but also to what we call higher-level judgements. Inspired by the study on 'very first impressions' by Bar, Neta, and Linz (2006, Emotion, 6, 269) the current research examined the speed and time course of three aspects of the aesthetic experience, namely beauty, specialness, and impressiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
(95 reference statements)
4
22
0
Order By: Relevance
“…Moreover, rating scores for pleasing were previously found to become higher with increasing exposure times (P. Locher et al., 2007 ). Together, these results support the notion that the aesthetic evaluation of artworks begins with the rapid bottom-up generation of a gist reaction ( Cupchik, Vartanian, Crawley, & Mikulis, 2009 ; P. Locher et al., 2007 ; Verhavert et al., 2018 ). This gist reaction may be followed by a more detailed exploration of pictorial detail, which is directed in a top-down fashion by cognition-based mechanisms, provided that cognitive information is relevant in the context of viewing the artwork.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, rating scores for pleasing were previously found to become higher with increasing exposure times (P. Locher et al., 2007 ). Together, these results support the notion that the aesthetic evaluation of artworks begins with the rapid bottom-up generation of a gist reaction ( Cupchik, Vartanian, Crawley, & Mikulis, 2009 ; P. Locher et al., 2007 ; Verhavert et al., 2018 ). This gist reaction may be followed by a more detailed exploration of pictorial detail, which is directed in a top-down fashion by cognition-based mechanisms, provided that cognitive information is relevant in the context of viewing the artwork.…”
Section: Discussionsupporting
confidence: 78%
“…A follow-up event-related potential study revealed a similar processing sequence of style following content ( Augustin, Defranceschi, Fuchs, Carbon, & Hutzler, 2011 ). The study by Verhavert et al. (2018) confirmed that consistent aesthetic judgments can be reached with a short glance at artworks of different styles.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This high level of agreement between the experiments (and between two independent groups of observers) suggests that both viewing durations were sufficient for participants to process artworks and rate their attractiveness. This is in line with previous reports showing that people are able to form a gist perception of artwork that is consistent across different presentation durations (Augustin, Defranceschi, Fuchs, Carbon, & Hutzler, 2011;Locher, 2015;Locher et al, 2007), or an aesthetic judgment in as brief as 30 ms (Verhavert et al, 2018). However, a recent study accentuated the individual differences rather than shared tastes in aesthetic ratings of artworks (Vessel, Maurer, Denker, & Starr, 2018).…”
Section: Correlation Of Aesthetic Ratings Across Experimentssupporting
confidence: 92%
“…Most investigations of serial dependence have used brief stimulus presentation times on the order of two to three hundred milliseconds, whereas we presented artworks for 1,000 ms in Experiment 1. Based on previous findings, this is more than long enough to make meaningful aesthetic judgments, which can be formed as quickly as 100 ms (Locher, Krupinski, Mello-Thoms, & Nodine, 2007) or even faster (Verhavert, Wagemans, & Augustin, 2018), but does this response time necessarily mean that the sequential bias of aesthetic judgments would occur quickly as well? With dissimilar exposure time to an artwork, the evidence available on which to base an aesthetic judgment would be qualitatively different, even if the same conclusion can be reached.…”
Section: Methodsmentioning
confidence: 99%